PENGARUH SOSIAL EKONOMI KELUARGA DENGAN PEMBERIAN STIMULASI TUMBUH KEMBANG PADA ANAK BALITA DI KOTA MOJOKERTO - Yuni Susanti, Ika (JURNAL KEPERAWATAN BINA SEHAT, 2015)
Children as candidate for the next generation need to get serious attention from the government of Indonesia. The quality of growth and development needs to be improved such as by getting proper nutrition, adequate stimulation and affordable quality health care, including detection and early intervention of growth and developmental aberrations. The data of Mojokerto in 2010 there were 9,130 targets of infants (aged 12-59 months). Based on the number of 7034 children (77.04%) have obtained the appropriate standard of care of infants. To determine the effect of family socioeconomic on the stimulation provision of growth and development in infants in Mojokerto. The Quasi-Experimental with Non-Equivalent Group Design. The population was mothers of infants aged 12-59 months. The intervention group and the control sample were 86 plus 5% used cluster random sampling. The independent variable: education in the mother, and the dependent variable: the stimulation provision of growth and development in infants, and external variable: family income, motherâs work, motherâs education and number of children. Univariable analysis used frequency distribution and mean, bivariate used t-test with significance level Ï-value-